2019
DOI: 10.1021/acssuschemeng.9b03113
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Graphene Oxide Nanofiltration Membranes for Black Liquor Concentration

Abstract: Black liquor (BL) concentration by multieffect evaporation is an extremely energy-intensive operation in the kraft pulping cycle. Membranes can significantly save energy in this process, but conventional membranes are strongly challenged by low solute rejections and poor stability in BL, which is a complex mixture containing dissolved lignin, other nonlignin organics, multiple inorganic salts at highly alkaline pH, and process temperatures of 70–85 °C. Here we describe in detail the fabrication, modification, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…The composition of the 15 wt% BL is reported in our previous work. [11] Roughly 5 wt% TS consists of lignin, 5 wt% of other organics (such as hemicellulose fragments The wide range of types and molecular weights (from ~100 to ~20 000) in BL, combined with the high pH and temperature, make membrane-based dewatering infeasible for conventional NF and RO membranes. However, we recently showed that GO NF membranes are remarkably functional and stable in BL conditions (pH ~13, temperature >70 C), and have reported detailed data on their performance.…”
Section: Go Membrane-based Bl Concentration Processesmentioning
confidence: 99%
See 3 more Smart Citations
“…The composition of the 15 wt% BL is reported in our previous work. [11] Roughly 5 wt% TS consists of lignin, 5 wt% of other organics (such as hemicellulose fragments The wide range of types and molecular weights (from ~100 to ~20 000) in BL, combined with the high pH and temperature, make membrane-based dewatering infeasible for conventional NF and RO membranes. However, we recently showed that GO NF membranes are remarkably functional and stable in BL conditions (pH ~13, temperature >70 C), and have reported detailed data on their performance.…”
Section: Go Membrane-based Bl Concentration Processesmentioning
confidence: 99%
“…However, we recently showed that GO NF membranes are remarkably functional and stable in BL conditions (pH ~13, temperature >70 C), and have reported detailed data on their performance. [10,11] Particularly, "GO-3" NF membranes are able to reject nearly all lignin, much of the other organics, and some of the inorganics (Table 2). They have an overall rejection of ~60% for divalent salts, ~70% for non-lignin organics, and little/no rejection of monovalent salts.…”
Section: Go Membrane-based Bl Concentration Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the developed membranes had a promising permeate flux of 24 L/m 2 ·h at 21.5 bar, and a total organic content rejection of 92%. Wang et al went in another direction and explored the possibility of enhancing polyether sulphone-supported membranes with graphene oxide [ 25 ]. With their membrane modification, they obtained a 99% rate of lignin rejection.…”
Section: Introductionmentioning
confidence: 99%